A whole cell fluorescence quenching-based approach for the investigation of polyethyleneimine functionalized silver nanoparticles interaction with Candida albicans - Tiwari, Atul Kumar; Gupta, Munesh Kumar; Narayan, Roger J.; Pandey, Prem C. (Frontiers in Microbiology, 2023)
This study used the intrinsic fluorescence of whole C. albicans cell as a molecular probe to understand the interaction dynamics of polyethyleneimine-functionalized silver nanoparticles. The results showed that synthesized PEI-f-Ag-NPs were ~5.6±1.2 nm in size and exhibited a crystalline structure. Furthermore, the recorded zeta potential (+18.2 mV) was associated with a strong electrostatic interaction between the cell and nanoparticle at the biological interface. Further, rapid killing kinetics was observed, with a remarkably low MIC value of 5µg/ml. PEI-f-Ag-NPs quenched the intrinsic fluorescence of C. albicans cells with increasing incubation time and concentration, indicating a fast and strong electrostatic interaction. The binding constant (Kb = 1 x 105 M -1, n=1.01) indicated strong binding of PEI-f-Ag-NPs with C. albicans surface. It should also be noted that the silver nanoparticles interacted more selectively with the tyrosine-rich proteins in the fungal cell. However, calcofluor fluorescence quenching showed non-specific binding on the cell surface. Thus, the antifungal mechanisms of PEI-f-Ag-NPs were observed as reactive oxygen species (ROS) overproduction. This study demonstrated the utility of fluorescence spectrophotometry for qualitative analysis of polyethyleneimine-functionalized silver nanoparticle interactions with Candida albicans.